North Atlantic Regional Water Resources Study report - North Atlantic Regional Water Resources Study Group.; North Atlantic Regional Water Resources Study Coordinating Committee. ([Washington, D.C.] : The Committee, 1972)
Cover title. Mode of access: Internet.